IMPLEMENTATION OF MADRASAH HEAD LEADERSHIP COMMUNICATION IN THE DEVELOPMENT OF RELIGIOUS CHARACTERS - Hamlan Andi Baso Malla (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
The purpose of this paper to analyze the communication headmaster duties and functions of leadership in the religious character building of students. Qualitative methods used scrutinize the meaning of the study contains analysis techniques of data reduction, data display and data verification. This paper has resulted in findings; First, communication headmaster leadership in carrying out duties effectively develop the religious character of learners. Second;religious character values ​​developed in the private learners were devout religious practices, mutual respect, social care, have an attitude of individual learning motivation and collaboration, and to produce an honest attitude, creative, responsible and inclusive on a private learners.